Demineralization-assisted porous carbon production from palm oil shell: Enhancing pore accessibility under low-severity conditions for sustainable applications - Arfiana; Era Restu Finalis; Ilhamsyah Noor; Fausiah; Ade Andini; Endro Wahju Tjahjono; Erbert Ferdy Destian; Dorit Bayu Islam Nuswantoro; Herson Bangun; Bagus Alif Firmandoko; Muhammad Dikdik Gumelar; Dita Adi Saputra; et al. (Chemosphere, 2026)

Integrated spatio-temporal DINEOF reconstruction under extreme cloud-induced data loss: application to MODIS chlorophyll-a in the eastern Indian Ocean - N. Nurhayati; M.N. Hidayat; R. Wafdan; N. Nizamuddin; J. Aminuddin; E. Yati; S. Rizal (International Journal of Remote Sensing, 2026)

Towards smart building envelopes: real-time monitoring of Overall Thermal Transfer Value (OTTV) through an intelligent management platform: a case study of UTM EcoHome - Anees Ahmed Vighio; Siti Maherah Hussin; Rozana Zakaria; Faridahanim Ahmad; Jam Shahzaib Khan; Eeydzah Aminuddin; Sheikh Ahmad Zaki; Nur Diyana Kamarudin; Melikuziev Mirkomil Vokhidjon Ugli; Omar Sedeeq Yousif (Energy and Buildings, 2026)

MFCC–ANN model for leak size estimation in pipeline systems - Mohd Fairusham Ghazali; Nor Azinee Said; Muhammad Hanafi Yusop; Erdiwansyah; Muhammad Aminuddin Pi Remli; Rizalman Mamat (Next Research, 2025)

Multiple magmatic processes and seawater circulation into the uppermost mantle of the Oman ophiolite: Evidence from Sr isotope and geochemical data for CM1A core samples from the Oman Drilling Project - Masako Yoshikawa; Tomoyuki Shibata; Ryoko Senda; Yumiko Harigane; Muhamad Asyraf Aminuddin; Tomoaki Morishita (Chemical Geology, 2025)

Corrigendum to “Development of thermal insulation sandwich panels containing end-of-life vehicle (ELV) headlamp and seat waste” [Waste Management 118 (2020) 402–415] - Yee Choong Wong; Norhayati Mahyuddin; Asrul Mahjuddin Ressang Aminuddin (Waste Management, 2025)

A framework for addressing water–rock interaction (WRI) for sustainable water resources development using various simulation models: Review - Naseem Akhtar; Abdassalam A. Azamzam; Saleh Ali Tweib; Hamza Mohamed Flafel; Dani Wijaya; Leila Bouida; Pahmi Husain; Shahwaz Khan; Mohd Talha Anees; Muhammad Irman Khalif Ahmad Aminuddin; Shubham Sharma; Rajesh Singh; et al. (Environment, Development and Sustainability, 2025)

Aflatoxin M 1 levels in urine and breast milk of lactating mothers in Kuala Lumpur, Malaysia - Alyaa Izzati Aminuddin; Rosita Jamaluddin; Mohd Redzwan Sabran; Nurul Husna Mohd Shukri (Food Additives & Contaminants: Part A, 2024)

Cadmium Associated Preeclampsia: A Systematic Literature Review of Pregnancy and Birth Outcomes - Fatima Sardar; Yuhaniza Shafinie Kamsani; Fathi Ramly; Nor Ashikin Mohamed Noor Khan; Razia Sardar; Anisa Aishah Aminuddin (Biological Trace Element Research, 2024)

Experimental investigation and performance evaluation of Samanea saman leaves and twigs gasification from urban residential garden waste as alternative future energy - Nina Konitat Supriatna; Prima Zuldian; Aminuddin; Ibrahim Purawiardi; Nabila Aprianti; Yohanes Gunawan; Oni Fariza; Alfonsus Agus Raksodewanto; Rizal Alamsyah; M. Hasanuzzaman; Adi Surjosatyo (Bioresource Technology Reports, 2024)

Mapping hotspots of tuberculosis cases with validation on site in Gombak, Selangor, Malaysia - Nur Adibah Mohidem; Malina Osman; Zailina Hashim; Farrah Melissa Muharam; Saliza Mohd Elias; Aminuddin Ma’pol (Spatial Information Research, 2024)

Development of convolutional neural network algorithm on ships detection in Natuna Islands-Indonesia using land look satellite imagery - Jamrud Aminuddin; R. Farzand Abdullatif; Mashuri; Eca Indah Anggraini; Syahrul Fadholi Gumelar; Ariantika Rahmawati (Remote Sensing Applications: Society and Environment, 2023)

U–Pb zircon geochronology and geochemistry of Luk Ulo River boulders belong to Late Cretaceous-Paleocene metapsammite and metagranite of Luk Ulo Karangsambung, Central Java, Indonesia - Muhammad Irman Khalif Ahmad Aminuddin; Mohd Shuaib; Naseem Akhtar; Nugroho Imam Setiawan; I. Wayan Warmada (Environmental Science and Pollution Research, 2023)

Evaluation of tree regression analysis for estimation of river basin discharge - Parveen Sihag; Ahmed Mohammed Sami Al-Janabi; Nashwan K. Alomari; Aminuddin Ab Ghani; Somvir Singh Nain (Modeling Earth Systems and Environment, 2021)

Regression models for sediment transport in tropical rivers - Mohd Afiq Harun; Mir Jafar Sadegh Safari; Enes Gul; Aminuddin Ab Ghani (Environmental Science and Pollution Research, 2021)

Electrospun Collagen Nanofibers and Their Applications in Skin Tissue Engineering - Jia Xian Law; Ling Ling Liau; Aminuddin Saim; Ying Yang; Ruszymah Idrus (Tissue Engineering and Regenerative Medicine, 2017)

Role of plasma-derived fibrin on keratinocyte and fibroblast wound healing - Jia Xian Law; Shiplu Roy Chowdhury; Bin Saim Aminuddin; Binti Haji Idrus Ruszymah (Cell and Tissue Banking, 2017)

The evaluation of cartilage differentiations using transforming growth factor beta3 alone and with combination of bone morphogenetic protein-6 on adult stem cells - C. C. Ude; H. C. Chen; M. Y. Norhamdan; B. M. Azizi; B. S. Aminuddin; B. H. I. Ruszymah (Cell and Tissue Banking, 2017)

Laboratory Evaluation of Metal Elements Urease Inhibitor and DMPP Nitrification Inhibitor on Nitrogenous Gas Losses in Selected Rice Soils - Rosmarina bt Ahmad Khariri; Mohd Khanif Yusop; Mohamed Hanafi Musa; Aminuddin Hussin (Water, Air, & Soil Pollution, 2016)

Prediction of temporal scour hazard at bridge abutment - Reza Mohammadpour; Aminuddin Ab. Ghani; Mohammadtaghi Vakili; Tooraj Sabzevari (Natural Hazards, 2016)

Methotrexate modulates the expression of MMP-1 and type 1 collagen in dermal fibroblast - Layla Nabai; Ruhangiz T. Kilani; Farzian Aminuddin; Yunyuan Li; Aziz Ghahary (Molecular and Cellular Biochemistry, 2015)

Prediction of water quality index in constructed wetlands using support vector machine - Reza Mohammadpour; Syafiq Shaharuddin; Chun Kiat Chang; Nor Azazi Zakaria; Aminuddin Ab Ghani; Ngai Weng Chan (Environmental Science and Pollution Research, 2015)

Markov CA, Multi Regression, and Multiple Decision Making for Modeling Historical Changes in Kirkuk City, Iraq - Najat Qader Omar; Mohd Sanusi S. Ahamad; Wan Muhd Aminuddin Wan Hussin; Narimah Samat; Siti Zubaidah Binti Ahmad (Journal of the Indian Society of Remote Sensing, 2014)

Comparison of the effects between animal-derived trypsin and recombinant trypsin on human skin cells proliferation, gene and protein expression - Maarof Manira; Khairoji Khairul Anuar; Wan Tai Seet; Abd Wahab Ahmad Irfan; Min Hwei Ng; Kien Hui Chua; Mohd. Yunus Mohd Heikal; Bin Saim Aminuddin; Bt Hj Idrus Ruszymah (Cell and Tissue Banking, 2014)

Suspended sediment load prediction of river systems: GEP approach - H. Md. Azamathulla; Yong Chong Cuan; Aminuddin Ab. Ghani; Chun Kiat Chang (Arabian Journal of Geosciences, 2013)

COMPUTATION OF DISCHARGE THROUGH SIDE SLUICE GATE USING GENE‐EXPRESSION PROGRAMMING - H. M. Azamathulla; Z. Ahmad; Aminuddin Ab. Ghani (Irrigation and Drainage, 2013)
The existing equations for the computation of discharge through a sluice gate are derived based on the statistical approach and implicit in form. This paper presents an intelligent prediction of discharge through a side sluice gate under free flow conditions using gene‐expression programming (GEP), which is an extension of genetic programming (GP). Considering the flow through a side sluice gate as orifice flow, a closed form equation for the prediction of discharge is derived. The coefficient of discharge is related to the approximate Froude number in the main channel and the ratio of upstream depth and gate opening. The proposed equation for the coefficient of discharge using GEP and available existing data produces better results ( R 2 = 0.935 and RMSE = 0.0658) compared to the existing equations for the side sluice gate. The computed coefficient of discharge is within ±5% of those observed for the data used for the validation of the proposed equation. The average percentage error in the coefficient of discharge computed using proposed equation is of the order of 2.15. Copyright © 2012 John Wiley & Sons, Ltd.

Genome-wide study identifies two loci associated with lung function decline in mild to moderate COPD - Nadia N. Hansel; Ingo Ruczinski; Nicholas Rafaels; Don D. Sin; Denise Daley; Alla Malinina; Lili Huang; Andrew Sandford; Tanda Murray; Yoonhee Kim; Candelaria Vergara; Susan R. Heckbert; et al. (Human Genetics, 2013)

Identification of suitable culture condition for expansion and osteogenic differentiation of human bone marrow stem cells - Shiplu Roy Chowdhury; Min Hwei Ng; Norazril Shamsul Abu Hassan; Bin Saim Aminuddin; Bt Hj Idrus Ruszymah (Human Cell, 2012)

Genetic association between human chitinases and lung function in COPD - F. Aminuddin; L. Akhabir; D. Stefanowicz; P. D. Paré; J. E. Connett; N. R. Anthonisen; J. V. Fahy; M. A. Seibold; E. G. Burchard; C. Eng; A. Gulsvik; P. Bakke; et al. (Human Genetics, 2012)

Gene-Expression Programming for the Development of a Stage-Discharge Curve of the Pahang River - Hazi Mohammad Azamathulla; Aminuddin Ab. Ghani; Cheng Siang Leow; Chun Kiat Chang; Nor Azazi Zakaria (Water Resources Management, 2011)

Prediction of total bed material load for rivers in Malaysia: A case study of Langat, Muda and Kurau Rivers - Aminuddin Ab. Ghani; H. Md. Azamathulla; Chun Kiat Chang; Nor Azazi Zakaria; Zorkeflee Abu Hasan (Environmental Fluid Mechanics, 2011)

Genetic Programming for Predicting Longitudinal Dispersion Coefficients in Streams - Hazi Mohammad Azamathulla; Aminuddin Ab. Ghani (Water Resources Management, 2011)

Molecular characterization of Cucumber mosaic virus infecting Gladiolus, revealing its phylogeny distinct from the Indian isolate and alike the Fny strain of CMV - Vimal Kumar Dubey; Aminuddin; Vijai Pal Singh (Virus Genes, 2010)

Production of phytoplasma-free plants from yellow leaf diseased Catharanthus roseus L. (G.) Don - S. K. Singh; Aminuddin; P. Srivastava; B. R. Singh; J. A. Khan (Journal of Plant Diseases and Protection, 2007)

Sensitive detection of a phytoplasma in Catharanthus roseus L. (G.) Don - J. A. Khan; S. K. Singh; P. Srivasthava; Aminuddin (Journal of Plant Diseases and Protection, 2006)

Training-induced increases in sea level V?O2 m a x and endurance are not enhanced by acute hypobaric exposure - D. L. Emonson; A. H. K. Aminuddin; R. L. Wight; G. C. Scroop; C. J. Gore (European Journal of Applied Physiology, 1997)

Substrate level versus oxidative phosphorylation in the generation of ATP in Thiobacillus denitrificans - M. Aminuddin (Archives of Microbiology, 1980)